mGlu5 Receptor Blockade Within the Nucleus Accumbens Shell Reduces Behavioral Indices of Alcohol Withdrawal-Induced Anxiety in Mice - Lee, Kaziya M.; Coelho, Michal A.; Class, MacKayla A.; Sern, Kimberly R.; Bocz, Mark D.; Szumlinski, Karen K. (Frontiers in Pharmacology, 2018)
Withdrawal from binge-drinking increases negative affect, coinciding with increased expression of the metabotropic glutamate receptor 5 (mGlu5) within the shell of the nucleus accumbens (AcbSh). Supporting a causal-effect relationship, systemic treatment with the mGlu5 receptor antagonist MTEP [3-((2-Methyl-4-thiazolyl)ethynyl)pyridine] is anxiolytic in binge-drinking adult and adolescent mice. Here, we employed neuropharmacological approaches to examine the functional relevance of AcbSh mGlu5 for behavioral indices of alcohol withdrawal-induced hyper-anxiety. Adult (PND 56) and adolescent (PND 28) male C57BL/6J mice consumed alcohol under modified Drinking-in-the-Dark procedures (10%, 20%, 40% alcohol v/v) for 14 days. At an alcohol withdrawal time-point when mice manifest robust behavioral signs of hyper-anxiety (1 and 28 days withdrawal for adults and adolescents, respectively), mice were infused intra-AcbSh with 0, 1 or 10 g MTEP and then affect was assayed in the light-dark shuttle box, marble-burying and forced swim tests. Brain tissue was collected to evaluate changes in Egr1 (early growth response protein 1) induction to index AcbSh neuronal activity. As expected, alcohol-experienced mice exhibited behavioral signs of hyper-emotionality. The anxiolytic effects of intra-AchSh MTEP were modest, but dose-dependent, and varied with age of drinking-onset. In adult-onset mice, only the 1 g MTEP dose reduced withdrawal-induced hyper-anxiety, whereas only the higher dose was effective in adolescent-onset animals. MTEP reduced Egr1 expression within the AcbSh, irrespective of alcohol drinking history or age of drinking-onset. However, only the high MTEP dose reduced Egr1 expression in adolescent-onset binging mice. These results implicate AcbSh mGlu5 in modulating alcohol withdrawal-induced negative affect and suggest age differences in the neurobiological effects of alcohol withdrawal and behavioral responsiveness to mGlu5 blockade within the AcbSh.